2014
DOI: 10.1149/2.0051414jes
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Monitoring of Electrochemical Oscillations during the Transition between Dense and Porous Anodic Silica Formation

Abstract: This study investigates the mechanism responsible for the electrochemical oscillations during silicon galvanostatic anodizing. Two oscillatory regimes of anodic silica formation in dilute fluoride electrolyte are monitored by combined in-situ curvature measurement and ellipsometry. At lower applied current density, a dense silica film is formed and the oscillations features are similar to those observed in fluoride-free electrolytes. At higher applied current density, a porous silica film is formed and the osc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The frequency of the respective oscillations varies depending on the system parameters. Owing to different electrochemical fingerprints, it had origi- nally been suggested that they involve inherently different electrochemical processes 16 , though later the interpretation was favoured that they emerge from the same mechanism 17,26 . In the following we demonstrate that LA oscillations and HA oscillations indeed live on different branches, and that the transition between both states occurs through complex oscillatory behaviour.…”
Section: A Cyclic Voltammetry and Oscillation Typesmentioning
confidence: 99%
“…The frequency of the respective oscillations varies depending on the system parameters. Owing to different electrochemical fingerprints, it had origi- nally been suggested that they involve inherently different electrochemical processes 16 , though later the interpretation was favoured that they emerge from the same mechanism 17,26 . In the following we demonstrate that LA oscillations and HA oscillations indeed live on different branches, and that the transition between both states occurs through complex oscillatory behaviour.…”
Section: A Cyclic Voltammetry and Oscillation Typesmentioning
confidence: 99%
“…where the parameters are defined above, eq. (6)(7)(8)(9)(10)(11)(12)(13)(14). The lines in Figure 9 represent the solutions for Q = 0 (eq.15), with the regions under the curve corresponding to the oscillatory region.…”
Section: Numerical Integration Of the Bz Reaction In The Oregonator Mmentioning
confidence: 99%
“…Consider, for instance, life organisms periodical phenomena, seasonal changes in leaf color, heartbeat rhythm, menstrual periods, and pattern formation in biological and geological systems [9][10]. Oscillations are also associated with metal dissolution processes [11]. Because of their broadly ranging implications, there has been a renewed interest in the long-time stability [12] of these systems and the details of the diffusion layer in the micrometer scale [13].…”
Section: Introductionmentioning
confidence: 99%